2021
DOI: 10.1108/jaee-09-2019-0173
|View full text |Cite
|
Sign up to set email alerts
|

Board characteristics, auditing characteristics and audit report lag in African Central Banks

Abstract: PurposeThe purpose of this paper is to examine the determinants of audit report lag in Sub-Saharan African Central Banks. In this case, the determinants were divided into two categories: independent variables and mediating variables. The independent variables, which were generated from board characteristics, included board size, board gender diversity, governor duality, audit committee size and audit committee meetings. The mediating variables were auditing characteristics and they comprised audit mandate, aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 102 publications
3
18
1
1
Order By: Relevance
“…Kaaroud et al (2020) found that the average delay in the audit report was 64 days. However, the number is lower than the delays reported by Chalu (2021) and Arda, Gororo, Grochalska, and Mohlala (2018) for African Central Banks, as well as that revealed by Zulfikar et al (2020) in Indonesia.…”
Section: Descriptive Statisticscontrasting
confidence: 61%
See 1 more Smart Citation
“…Kaaroud et al (2020) found that the average delay in the audit report was 64 days. However, the number is lower than the delays reported by Chalu (2021) and Arda, Gororo, Grochalska, and Mohlala (2018) for African Central Banks, as well as that revealed by Zulfikar et al (2020) in Indonesia.…”
Section: Descriptive Statisticscontrasting
confidence: 61%
“…Audit report lag is defined as the length of time from a company's fiscal year-end to the audit report date (Chalu, 2021;Ishaku, Abdulkarim, & Mohammed, 2021;Ismail, Mansour, & Sayed, 2022;Kaaroud et al, 2020;Zulfikar et al, 2020). The maximum legal period to issue an audit report varies according to the country's respective laws.…”
Section: Reporting Delaymentioning
confidence: 99%
“…Indeed, this measure has been used by Barako and Brown (2008) and Prado-Lorenzo and Garcia-Sanchez (2010). Chalu (2021) finds that board gender diversity has a significant negative effect on ARL .…”
Section: Methodsmentioning
confidence: 99%
“…H1: Return on assets has an impact on audit report latency. Chalu (2021) and Habib, Bhuiyan, Huang, and Miah (2019) found that the size of the board members had a positive effect on the audit report latency. In this context, the second hypothesis of the research was formed as follows.…”
Section: Extended Abstract Geni̇şleti̇lmi̇ş öZetmentioning
confidence: 99%